Auxin signaling and vascular cambium formation enable storage metabolism in cassava tuberous roots - Rüscher, David; Corral, José María; Carluccio, Anna Vittoria; Klemens, Patrick A. W.; Gisel, Andreas; Stavolone, Livia; Neuhaus, H. Ekkehard; Ludewig, Frank; Sonnewald, Uwe; Zierer, Wolfgang (Journal of Experimental Botany, 2021)
Cassava storage roots are among the most important root crops worldwide, and represent one of the most consumed staple foods in sub-Saharan Africa. The vegetatively propagated tropical shrub can form many starchy tuberous roots from its stem. These storage roots are formed through the activation of secondary root growth processes. However, the underlying genetic regulation of storage root development is largely unknown. Here we report distinct structural and transcriptional changes occurring during the early phases of storage root development. A pronounced increase in auxin-related transcripts and the transcriptional activation of secondary growth factors, as well as a decrease in gibberellin-related transcripts were observed during the early stages of secondary root growth. This was accompanied by increased cell wall biosynthesis, most notably increased during the initial xylem expansion within the root vasculature. Starch storage metabolism was activated only after the formation of the vascular cambium. The formation of non-lignified xylem parenchyma cells and the activation of starch storage metabolism coincided with increased expression of the KNOX/BEL genes KNAT1, PENNYWISE, and POUND-FOOLISH, indicating their importance for proper xylem parenchyma function.
CRIS-Team WoS Importer:2021-07-02

Carbon usage in yellow-fleshed Manihot esculenta storage roots shifts from starch biosynthesis to cell wall and raffinose biosynthesis via the myo-inositol pathway - Gutschker, Sindy; Rüscher, David; Rabbi, Ismail Y.; Rosado-Souza, Laise; Pommerrenig, Benjamin; Pauly, Markus; Robertz, Stefan; van Doorn, Anna M.; Schlereth, Armin; Neuhaus, H. Ekkehard; Fernie, Alisdair R.; Reinert, Stephan; et al. (Plant Journal, 2024)
Cassava is a crucial staple crop for smallholder farmers in tropical Asia and Sub-Saharan Africa. Although high yield remains the top priority for farmers, the significance of nutritional values has increased in cassava breeding programs. A notable negative correlation between provitamin A and starch accumulation poses a significant challenge for breeding efforts. The negative correlation between starch and carotenoid levels in conventional and genetically modified cassava plants implies the absence of a direct genomic connection between the two traits. The competition among various carbon pathways seems to account for this relationship. In this study, we conducted a thorough analysis of 49 African cassava genotypes with varying levels of starch and provitamin A. Our goal was to identify factors contributing to differential starch accumulation. Considering carotenoid levels as a confounding factor in starch production, we found that yellow- and white-fleshed storage roots did not differ significantly in most measured components of starch or de novo fatty acid biosynthesis. However, genes and metabolites associated with myo-inositol synthesis and cell wall polymer production were substantially enriched in high provitamin A genotypes. These results indicate that yellow-fleshed cultivars, in comparison to their white-fleshed counterparts, direct more carbon toward the synthesis of raffinose and cell wall components. This finding is underlined by a significant rise in cell wall components measured within the 20 most contrasting genotypes for carotenoid levels. Our findings enhance the comprehension of the biosynthesis of starch and carotenoids in the storage roots of cassava.
CRIS-Team Scopus Importer:2024-07-12
Keywords: carotenoid content; cassava; cell wall components; Manihot esculenta; myo-inositol; provitamin A; raffinose; starch content

Efficient sugar utilization and transition from oxidative to substrate-level phosphorylation in high starch storage roots of African cassava genotypes - Lamm, Christian; Rabbi, Ismail Y.; Medeiros, David Barbosa; Rosado-Souza, Laise; Pommerrenig, Benjamin; Dahmani, Ismail; Rüscher, David; Hofmann, Jörg; van Doorn, Anna M.; Schlereth, Armin; Neuhaus, H. Ekkehard; Fernie, Alisdair R.; et al. (Plant Journal, 2023)
Cassava's storage roots represent one of the most important sources of nutritional carbohydrates worldwide. Particularly, smallholder farmers in sub-Saharan Africa depend on this crop plant, where resilient and yield-improved varieties are of vital importance to support steadily increasing populations. Aided by a growing understanding of the plant's metabolism and physiology, targeted improvement concepts already led to visible gains in recent years. To expand our knowledge and to contribute to these successes, we investigated storage roots of eight cassava genotypes with differential dry matter content from three successive field trials for their proteomic and metabolic profiles. At large, the metabolic focus in storage roots transitioned from cellular growth processes toward carbohydrate and nitrogen storage with increasing dry matter content. This is reflected in higher abundance of proteins related to nucleotide synthesis, protein turnover, and vacuolar energization in low starch genotypes, while proteins involved in sugar conversion and glycolysis were more prevalent in high dry matter genotypes. This shift in metabolic orientation was underlined by a clear transition from oxidative- to substrate-level phosphorylation in high dry matter genotypes. Our analyses highlight metabolic patterns that are consistently and quantitatively associated with high dry matter accumulation in cassava storage roots, providing fundamental understanding of cassava's metabolism as well as a data resource for targeted genetic improvement.
CRIS-Team Scopus Importer:2023-07-21
Keywords: energy metabolism; glycolysis; Manihot esculenta; metabolomics; oxidative phosphorylation; proteomics; source/sink; starch metabolism; sugar metabolism; TCA-cycle

Symplasmic phloem loading and subcellular transport in storage roots are key factors for carbon allocation in cassava - Rüscher, David; Vasina, Viktoriya V.; Knoblauch, Jan; Bellin, Leo; Pommerrenig, Benjamin; Alseekh, Saleh; Fernie, Alisdair R.; Neuhaus, H. Ekkehard; Knoblauch, Michael; Sonnewald, Uwe; Zierer, Wolfgang (Plant Physiology, 2024)
Cassava (Manihot esculenta) is a deciduous woody perennial shrub that stores large amounts of carbon and water in its storage roots. Previous studies have shown that assimilating unloading into storage roots happens symplasmically once secondary anatomy is established. However, mechanisms controlling phloem loading and overall carbon partitioning to different cassava tissues remain unclear. Here, we used a combination of histological, transcriptional, and biochemical analyses on different cassava tissues and at different timepoints to better understand source–sink carbon allocation. We found that cassava likely utilizes a predominantly passive symplasmic phloem loading strategy, indicated by the lack of expression of genes coding for key players of sucrose transport, the existence of branched plasmodesmata in the companion cell/bundle sheath interface of minor leaf veins, and very high leaf sucrose concentrations. Furthermore, we showed that tissue-specific changes in anatomy and non-structural carbohydrate contents are associated with tissue-specific modification in gene expression for sucrose cleavage/synthesis, as well as subcellular compartmentalization of sugars. Overall, our data suggest that carbon allocation during storage root filling is mostly facilitated symplasmically and is likely mostly regulated by local tissue demand and subcellular compartmentalization.
CRIS-Team Scopus Importer:2024-10-11

Tuber and Tuberous Root Development - Zierer, Wolfgang; Rüscher, David; Sonnewald, Uwe; Sonnewald, Sophia (Annual Review of Plant Biology, 2021)
Root and tuber crops have been an important part of human nutrition since the early days of humanity, providing us with essential carbohydrates, proteins, and vitamins. Today, they are especially important in tropical and subtropical regions of the world, where they help to feed an ever-growing population. Early induction and storage organ size are important agricultural traits, as they determine yield over time. During potato tuberization, environmental and metabolic status are sensed, ensuring proper timing of tuberization mediated by phloem-mobile signals. Coordinated cellular restructuring and expansion growth, as well as controlled storage metabolism in the tuber, are executed. This review summarizes our current understanding of potato tuber development and highlights similarities and differences to important tuberous root crop species like sweetpotato and cassava. Finally, we point out knowledge gaps that need to be filled before a complete picture of storage organ development can emerge.
CRIS-Team Scopus Importer:2021-07-02
Keywords: cassava; development; potato; storage root; sweetpotato; tuber